Flumioxazin Tank-Mixtures with Six Herbicides for Annual Bluegrass (Poa annua) Control in Bermudagrass. (September 2015) - Reed, Thomas V.; McCullough, Patrick E.; Grey, Timothy; Czarnota, Mark A.; Vencill, William K.; Waltz, F. Clint
Abstract : Flumioxazin is a protoporphyrinogen oxidase inhibitor with potential for POST annual bluegrass control and PRE smooth crabgrass control in bermudagrass. However, flumioxazin applications are often less effective in winter, compared with fall, because of reduced efficacy on mature annual bluegrass. The objective of this research was to evaluate tank-mixtures of flumioxazin with six other herbicide mechanisms of action for POST annual bluegrass control in late winter and residual smooth crabgrass control. Flumioxazin at 0 or 0.42 kg ai ha −1 was evaluated in combination with flazasulfuron at 0.05 kg ai ha −1, glufosinate at 1.26 kg ai ha −1, glyphosate at 0.42 kg ae ha −1, mesotrione at 0.28 kg ai ha −1, pronamide at 1.68 kg ai ha −1, or simazine at 1.12 kg ai ha −1 . Flumioxazin alone controlled annual bluegrass 61 to 70% at 8 wk after treatment (WAT) in three experiments from 2012 to 2014 in central Georgia. Flumioxazin tank-mixed with flazasulfuron, glyphosate, glufosinate, pronamide, and simazine provided good (80 to 89%) to excellent (> 90%) control of annual bluegrass at 8 WAT in 2 of 3 yr. These tank-mixtures were also more effective than flumioxazin alone in 2 of 3 yr, and control was greater or equal to the tank-mix partners applied alone. Treatments that included flumioxazin provided excellent (≥ 90%) control of smooth crabgrass at 6 mo after treatment in all 3 yr. Overall, tank-mixing flumioxazin with other herbicide chemistries may improve POST annual bluegrass control, compared with exclusive treatments, and effectively control smooth crabgrass in bermudagrass.